STUDY OF PARAMETERS FOR EVALUATION OF SOFTWARE AS A SERVICE (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Cloud computing is widely believed to be a revolution in computing that could soon become an industry standard, altogether replacing the traditional office setup. Due to the recency of these services, question marks exist over the performance of these systems, and consequently, over the corresponding billing schemes that the service provider issues. This study aims at addressing some of these doubts by introducing a measurement test for the network performance of these services, and comparing them with the performance offered by traditional web-hosting services. In this paper the parameters to be taken into consideration are studied and evaluated when actually one is going for purchasing software as a service, so that true value and benefits can be understood.